Land Use Zoning Management to Coordinate the Supply–Demand Imbalance of Ecosystem Services: A Case Study in the City Belt Along the Yellow River in Ningxia, China - Lyu, Rongfang; Clarke, Keith C.; Tian, Xiaolei; Zhao, Wenpeng; Pang, Jili; Zhang, Jianming (Frontiers in Environmental Science, 2022)
The imbalance between the supply and demand of ecosystem services (ESs) is one of the main reasons for ecological degradation, which significantly impacts human well-being and ecological safety. Spatial heterogeneity of ES supply-demand, ES trade-offs and socio-ecological environment calls for zoning management, while rare studies have combined the above three aspects in dividing management zones and proposing strategies. Using the City Belt along the Yellow River in Ningxia (CBYN) in northwestern China as a case study, this study quantified the supply and demand for five key ESs (crop production, carbon sequestration, nutrient retention, sand fixation and recreational opportunity), analyzed ES trade-offs/synergies and bundles through correlation analysis and the Self-Organizing Mapping (SOM) method, and investigated their socio-ecological driving mechanisms through a Random Forest model and SOM method. Management zones and differentiated suggestions were proposed through overlaying ES bundles and driver clusters. The results suggested that crop production, carbon sequestration and nutrient retention were mostly correlated to the same intrinsic ecological process, resulting in consistent synergies among these three ESs at both supply and demand sides. On the contrary, the variance in interactions between the two ESs of sand fixation and recreational opportunity and the other three ESs can be owe to the low similarities in their intrinsic ecological process and external driving mechanisms. Fourteen socio-ecological factors could effectively explain the spatial heterogeneity of ES supply, demand and match degree. Fourteen management zones with similar ecological problem and socio-ecological environment were delineated, and differentiated suggestions were proposed for each zone. Adopting both ES characteristics and socio-ecological environment into zoning management could effectively detect ecological problem and help to promote management suggestions in different socio-ecological contexts. This framework could offer new insights for integrating ESs into actual decision-making and ecosystem management.